Effect of the frying process on the properties of gluten protein of you-tiao. (25th April 2020) - Zhou, Ruoxin; Sun, Juan; Qian, Haifeng; Li, Yan; Zhang, Hui; Qi, Xiguang; Wang, Li
Highlights: Frying induced gluten protein unfolding, decomposition, and reaggregation. The proportions of β-sheets increased at the cost of β-turns after frying. Frying contributed to the disulfide bond formation of gluten. Frying destroyed most of the non-covalent bonds. Frying weakened the flexibility of protein chain, leading to a looser gluten network. Abstract: Wheat is one of the most important grains in cereal products. Gluten protein is an important component of wheat and plays an important role in the human diet. The variations of gluten protein in you-tiao were investigated in this study during frying, with a view toward a theoretical basis for the improvement of processing methods and quality in you-tiao. During the processing of you-tiao, gluten protein altered significantly. Analysis of secondary structure and surface hydrophobicity indicated that gluten protein molecules were unfolded and decomposed after frying, providing the opportunity for protein reaggregation. The extractability and sodium dodecyl sulphate-polyacrylamide gel electrophoresis profiles demonstrated the decomposition and reaggregation of gluten protein. Analysis of the chemical interactions proved that gluten protein molecules aggregated mainly by disulfide bonds and hydrophobic interactions. Frying induced a loose and uneven gluten network.